2021
DOI: 10.3390/cmd2010005
|View full text |Cite
|
Sign up to set email alerts
|

The Stability and Chloride Entrapping Capacity of ZnAl-NO2 LDH in High-Alkaline/Cementitious Environment

Abstract: In this work, the ZnAl-NO2 LDH (layered double hydroxide) is investigated as a possible additive for mitigating the chloride-induced corrosion of steel in reinforced concrete. The investigation focused on the stability and chloride binding capacity of this LDH in the pH range typical of cementitious materials. Until pH = 12.5 the material was stable and effective in capturing chloride ions from the surrounding aqueous environment. For higher pH, precisely that of hydrated cement, the LDH was partially dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Therefore, these results evidently show that the release behavior of FA from LDH-FA hinges on the pH of the release environment. The high structural stability of LDHs in the high alkaline range is also in good agreement with a previous study [27].…”
Section: Crf Study Of Fa Release From the Ldh-fa Nanocompositesupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, these results evidently show that the release behavior of FA from LDH-FA hinges on the pH of the release environment. The high structural stability of LDHs in the high alkaline range is also in good agreement with a previous study [27].…”
Section: Crf Study Of Fa Release From the Ldh-fa Nanocompositesupporting
confidence: 92%
“…Due to this reason, Cl − will have a lower affinity towards the positively charged layer of LDH, thereby undergoing an anion exchange process in a slower manner than the polyatomic OH − and PO 4 3− anions. A recent study has reported that LDH tends to have higher selectivity towards OH − than Cl − [27]. The order of anion selectivity can be arranged according to their affinity toward LDH, in the sequence of CO 3 2− > OH − > F − > Cl − > Br − > NO 3 − , with CO 3 2− being the most preferable anions by LDH [28].…”
Section: Crf Study Of Fa Release From the Ldh-fa Nanocompositementioning
confidence: 99%